(untitled) (Research, Society and Development, 2022)
The monitoring growth and development is an excellent assistance structured practice of the National Policy for Integral Attention to Children’s Health. Health technologies, such as the Child’s Handbook, corroborate this practice and favor childcare. The objective of this study was to identify and map health technologies for growth monitoring and development of infants. This is a scope review based on the assumptions of the Joanna Briggs Institute according to Preferred Reporting Items for Systematic Review and Meta-analyses extension for Scoping Reviews. The research protocol was registered in the Open Science Framework (https://osf.io/2b5sz/), under DOI identification: 10.17605/OSF.IO/2B5SZ. Scientific manuscripts, theses, and dissertations were analyzed in 11 national and international databases using the PCC mnemonic: P Population – Health technologies; C Concept – Growth and development; C Context – Infant. Inclusion criteria were researches that met the objective of the study, published online, available in full text, and no restriction of time limit; and exclusion criteria were editorials, theoretical tests, and duplicate studies. For this, 61 studies were selected to compose the sample, published from 2018 to 2022. The results showed that about the tools, assistive technology corresponded to 48%, with hard technologies standing out (84%) and the implementation phase prevailing. In addition, 41% of the technologies were intended for health professionals, while the applications were mainly intended for users with a care focus. Thus, despite financial and integration challenges, the technologies implementation favors the accessibility and quality of care and, therefore, a better quality of life.